ANALISIS STRUKTUR DAN FUNGSI GEGURITAN NAGA PUSPA KARYA I NYOMAN SUPRAPTA - Rarasathi, Ida Ayu Diah (Humanis; Volume 5. No. 1. Oktober 2013)
The research of structure and function of Geguritan Naga Puspa purposes describe the structure which forms that geguritan and the functions which are contained in it. The theories which are used theory of structural and theory of function. Theory of structural which is used the theory that proposed by Teeuw. Analyze the function used the theory that proposed by Endraswara. Method and technique which are used on this research is stage of providing data, stage of analyzing data, and stage of presenting the result of analyzing data. Stage of providing the data, it uses observation method and note taking technique. Stage of analyzing data, it uses qualitative method and descriptive analytical technique. Stage of presenting the result of analyzing data, it uses informal methods and also inductive and deductive techniques.The result of this research, are the forma structure and narrative structure. Forma structure which language convention, such as using of pupuh, language style, and variety of language. Narrative structure which literature convention generally such plot, setting, character, theme, and message, and also literature convention specifically which fictitious elements which contain mythology, legendary,  hagiography, and symbolism. The function which is contained, such as historical function, as an honor to Ida Sang Hyang Widhi, as an honor to ancestors, and as media education based on Hinduism.
Keywords: geguritan, structure, and function